2019
DOI: 10.4236/jep.2019.1010078
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Content in Electronic Cigarette Refill Solutions and Its Release in Aerosols

Abstract: Electronic cigarette (EC) is a device that imitates conventional cigarettes, which vaporizes a solution, with or without nicotine. This study evaluates the nicotine levels in EC refill solutions, its release in aerosols and comparison to the amount stated on the label. Seventy-two (72) different EC refill solutions were obtained from local shops in Selangor, Malaysia consisting of 40 nicotine-containing (3-12 mg) and 32 nicotine-free (0 mg) solutions. Aerosols were obtained by using an air tight syringe connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Nicotine poisoning due to cigarettes is rare; however, ECs may pose an increased risk of nicotine toxicity due to higher nicotine concentrations in the e‐liquids and cartridges as well as higher nicotine availability due to lack of combustion 65 . Additionally, the level of nicotine exposure from each puff is highly variable, there is variability in aerosolization and inconsistent nicotine delivery, many studies have found 4,45,71,72 . The FDA has claimed: ‘There is too much variability in the amount of nicotine delivered per puff of any e‐cigarette cartridge for them to be considered safe’.…”
Section: Toxicological Effects Of E‐cigarettesmentioning
confidence: 99%
“…Nicotine poisoning due to cigarettes is rare; however, ECs may pose an increased risk of nicotine toxicity due to higher nicotine concentrations in the e‐liquids and cartridges as well as higher nicotine availability due to lack of combustion 65 . Additionally, the level of nicotine exposure from each puff is highly variable, there is variability in aerosolization and inconsistent nicotine delivery, many studies have found 4,45,71,72 . The FDA has claimed: ‘There is too much variability in the amount of nicotine delivered per puff of any e‐cigarette cartridge for them to be considered safe’.…”
Section: Toxicological Effects Of E‐cigarettesmentioning
confidence: 99%